Fast quantitative 3D ultrashort echo time MRI of cortical bone using extended cones sampling. Issue 1 (28th February 2019) - Wan, Lidi; Zhao, Wei; Ma, Yajun; Jerban, Saeed; Searleman, Adam C.; Carl, Michael; Chang, Eric Y.; Tang, Guangyu; Du, Jiang
Abstract : Purpose: To investigate the effect of stretching sampling window on quantitative 3D ultrashort TE (UTE) imaging of cortical bone at 3 T. Methods: Ten bovine cortical bone and 17 human tibial midshaft samples were imaged with a 3T clinical MRI scanner using an 8‐channel knee coil. Quantitative 3D UTE imaging biomarkers, including T1, T 2 ∗, magnetization transfer ratio and magnetization transfer modeling, were performed using radial or spiral Cones sampling trajectories with various durations. Errors in UTE‐MRI biomarkers as a function of sampling time were evaluated using radial sampling as a reference standard. Results: For both bovine and human cortical bone samples, no significant differences were observed for all UTE biomarkers (single‐component T 2 ∗, bicomponent T 2 ∗ and relative fractions, T1, magnetization transfer ratio, and magnetization transfer modeling of macromolecular fraction) for spiral sampling windows of 992 µs to 1600 µs compared with a radial sampling window of 688 µs. Conclusion: The total scan time can be reduced by 76% with quantification errors less than 5%. Quantitative UTE‐MRI techniques can be greatly accelerated using longer sampling windows without significant quantification errors.